Profile of Students’ Argumentation Ability Based On Adversity Quotient In Statistical Problem - Zuhadur Ra'is Ariyono Putra; Rustanto Rahardi; Sisworo Sisworo; Hendro Permadi (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
Argumentative ability can be seen from the argumentation pattern that appears. This pattern needs to be evaluated to look over the quality of the argumentation to make the right problem-solving. This evaluation can be done by recognizing the components that make up the argument. This study goals to describe students' argumentation abilities in solving statistical problem based on Adversity Quotients (AQ). This qualitative descriptive research elaborated 39 students taking a statistical methods course. Subjects were grouped into three types of Adversity Quotient based on the ARP (Adversity Response Profile) questionnaire results. Data were obtained using statistical problem tests and interviews. The outcomes showed three levels of AQ found in students, namely Camper, Toward Climber, and Climber. Camper-type students bring up the Claim-Data-Warrant pattern. Students with AQ levels towards climbers tend to have the same pattern as the Camper type. In comparison, students with the AQ Climber type have a Claim-Data-Warrants-Backing pattern. Based on the outcomes of the study, it can see that students' argumentation skills are determined by the Adversity Quotient level they have when solving statistical problems.